Relación altura comercial – diámetro en el crecimiento de los árboles en tres especies de la familia botánica Euphorbiaceae. Puerto Almendra, Loreto, Perú - 2021 - Saldaña Dávila, Piero Junior (2022)
The investigation was carried out in the Arboretum "El Huayo" of CIEFOR Puerto Almendra - FCF - UNAP, district of San Juan Bautista, Maynas province, Loreto region. The objective was to determine the commercial height - diameter relationship in trees of the botanical family Euphorbiaceae. In the data recording, the commercial height and the diameter at breast height (DBH) of the trees of three species with DBH ? 10 cm were considered. The results indicate that the allometric model that best adjusted to the commercial height - diameter relationship was the cubic one in the Conceveiba martiana Baill “Sacha zapote” species; Croton schiedeanus Schltdl "Sacha quinilla" and Micrandra spruceana (Baill.) R. E. Schult "Shiringa masha" of the botanical family Euphorbiaceae; They also presented from fair to excellent for the commercial height - diameter ratio.